Communication and E-Government: The Case Study of E-Government Implementation in Tourism Communications in the Tourism Department, Daerah Istimewa Yogyakarta (DIY) Province - Rosalia Prismarini Nurdiarti; Didik Haryadi Santoso (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2018)
The development of Digital Government Services (DGS) is a form of bureaucratic transfor-mation. This research focuses on virtual digital technology used in the government, especially in the tourism office department of Yogyakarta special administrative region which is also known as Daerah Istimewa Yogyakarta (DIY) Province. Based on Ministry of Communication and Information (MoCI) 2012 report, e-Government adoption in DIY was ranked 4th in the country. The province has the vision of becoming a cyber province as one of the ways to fulfil the needs of its residents. The objectives of this study encompass: 1) description of the imple-mentation of e-government in DIY Tourism department; 2) mapping and utilizing the tourism communication strategies to identify e-government implementation in the Tourism department; and 3) assess the role that e-government technology adoption can help to strengthen service encouraging the enhancement of service and creative industries towards contributing to im-prove the higher tourism development in DIY. The research used a case study approach with data collected using informal interview and documentation. Results of the research showed that: 1) the expertise in information and communication technology (ICT) is pivotal for was necessary for the development of ing the tourism-based websites and e-government applica-tions; 2) the importance of developing multimedia-based content to ensure relevant and updat-ed content; and 3) the importance of taking into account the needs and interests of undergradu-ates and undergraduate audience in developing and adoption of e-government services because they constitute the largest segment that uses the virtual digital government services.